Designing social protection for climate adaptation, poverty reduction, gender equality - Roy, Shalini; Hidrobo, Melissa; Bryan, Elizabeth; Nesbitt-Ahmed, Zahrah; Läderach, Peter; Mueller, Valerie; Campbell, Raramai (CGIAR System Organization, 2024)
Guidance on social protection design for implementers and donors to build synergies between climate adaptation, poverty reduction, and gender equality.